Traumatic Knee Injuries in Lattakia City Club Players: An Analytic Study - علي ناظم (Latakia University Journal -Medical Sciences Series, 2020)
The research is considered an analytic study which aims to know different kinds of knees injuries which some Lattakia city club players have, and the reasons behind them and the places they occur in. The study covered the city club players and aimed to reach preventive foundations the training program may contain. The study also contains recommendations associated with the infrastructure in the place of training. The study have involved (200) scorbutics The results were as follows: - The injuries biggest rate is in athletics then comes the gymnasium. - The most important reasons are overheating shortage and the lack of preparation. - The given rest period is not enough as well as the period of physical treatment and the sessions number. - The absence of first aid when the injury occurs.